Association between Indoor Environment, Blood Trace Elements, and Immune Globulin among Workers from Vegetables Plastic Greenhouses in Yinchuan, China - Honghui Li; Jiangping Li; Wei Sun; Lijun Dong; Lingqin Zhu; Zhen Jiang; Huifang Yang (Tehran University of Medical Sciences, 2022)
Background: To study the association between indoor environment (MiE), blood trace elements (BTE), and immune globulin (PRO) among workers from vegetables plastic greenhouse, and to assess the mediate effects on MiE and PRO by BTE. Methods: Overall, 168 practitioner and corresponding sheds were included from cross-sectional study in 2016. BTE and PRO were determined by physical test and MiE data from field and laboratory measurement. The association was assessed using canonical correlation analysis. The direct and indirect effects between MiE, PRO and BTE were conducted by structural equation model. 5000 times bootstrap methods were performed to estimate coefficient and 95% confidence interval. Results: MiE was moderately correlated with BTE (canonical coefficient = 0.439), and BTE was strongly correlated with PRO (canonical coefficient = 0.514 and 0.481). No statistical evidence was found for the overall impact of MiE on PRO, and BTE as an intermediary affecting its relevance was not confirmed. Only the path way of the BTE impact on PRO had a significant positive effect (P=0.012). Conclusion: BTE was positively associated with PRO, therefore, reducing exposure in greenhouse is a pathway to remain blood trace elements, and further effect the immune protein in human body.